Immunomodulation exerted by galectins: a land of opportunity in rare cancers - Díaz-Alvarez, Laura; López-Cortés, Georgina I.; Pérez-Figueroa, Erandi (Frontiers in Immunology, 2023)
Rare cancers represent only 5% of newly diagnosed malignancies. However, in some cases, they account for up to 50% of the deaths attributed to cancer in their corresponding organ. Part of the reason is that treatment options are generally quite limited, non-specific, and very often, only palliative. Needless to say, research for tailored treatments is warranted. Molecules that exert immunomodulation of the tumor microenvironment are attractive drug targets. One such group is galectins. Thus, in this review we summarize the current knowledge about galectin-mediated immunomodulation in rare cancers, highlighting the research opportunities in each case.